Totally Umbilical Lightlike Hypersurfaces in Robertson-Walker Spacetimes. (18th March 2014) - Dong, Junhong; Liu, Ximin
Abstract : We study the problem of lightlike hypersurface immersed into Robertson-Walker (RW) spacetimes in this paper, where the screen bundle of the hypersurface has constant higher order mean curvature. We consider the following question: under what conditions is the compact lightlike hypersurface totally umbilical? Our approach is based on the relationship between the lightlike hypersurface with its screen bundle and the Minkowski formulae for the screen bundle.